2017
DOI: 10.5468/ogs.2017.60.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the placenta

Abstract: Autophagy is an evolutionarily conserved catalytic process by which cytoplasmic components including damaged macromolecules and organelles are degraded. The role of autophagy includes adaptive responses to nutrition deprivation or intracellular stimuli. Although autophagosomes were first observed in early 1960s, it was 1990s that autophagy-related genes in yeast were identified and studied. Nowadays, the molecular machinery of autophagy and signaling pathway to various stimuli are almost outlined. Dysregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 136 publications
(182 reference statements)
1
41
0
Order By: Relevance
“…One such mechanism that the placenta may undertake to reduce its own cellular energy requirements is autophagy, which is known to be activated during times of stress (for example, hypoxia, changes in resource availability, and inflammatory injury) [ 42 ]. As a critical regulator of autophagy, AMPKα controls numerous cellular pathways that promote autophagosome development, reduce inflammatory signaling, and suppress protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One such mechanism that the placenta may undertake to reduce its own cellular energy requirements is autophagy, which is known to be activated during times of stress (for example, hypoxia, changes in resource availability, and inflammatory injury) [ 42 ]. As a critical regulator of autophagy, AMPKα controls numerous cellular pathways that promote autophagosome development, reduce inflammatory signaling, and suppress protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the high metabolic capacity and demand of the male placenta in the current study, autophagy markers were upregulated in the female placenta. Autophagy is a cellular defense mechanism that may serve to protect basal cellular function in the face of nutrient deprivation and/or during inflammatory stress [ 42 ]. Thus, predictably, elevated levels of autophagy have been observed in placentae from pregnancies complicated with preeclampsia and in rodent models of acute maternal food deprivation [ 42 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is understood as a mechanism for both cell death and cytoprotection depending on the cellular types and contexts, and it has been implicated in various physiological and pathological conditions 6 , 7 . Without exception, autophagy is also involved in numerous physiological and pathological processes of human reproduction and pregnancy complications 8 11 . Undue autophagic activity upon non-physiological stimuli such as excessive inflammation or severe oxidative stress may limit trophoblast invasion, resulting in defective placentation 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an evolutionarily conserved catalytic process by which cytoplasmic components including damaged macromolecules and organelles are degraded 43 . An increased autophagosome formation was observed in placenta from preeclampsia and FGR 44 . In this study, we found LC3-II expression was elevated in placenta from ICP.…”
Section: Discussionmentioning
confidence: 91%